in, the, in, of, the, of, and, i Aliens Intervention in the State Conflict in International Law (Study of the Engagement of America, Saudi Arabia, Russia, and Iran in the Arab Spring Conflict) - Ridwan Arifin; Mumpuni Tri Utami; Ahmad Zaharuddin Sani Ahmad Sabri (Fakultas Hukum Universitas Hang Tuah, 2020)
Various conflicts experienced by the state are denied or there are no interventions from other countries both on a large and small scale, either directly or indirectly. Interventions have the meaning of dictatorial interference by a country against other countries’ internal affairs. This has caused controversy because it is contrary to the principle of state sovereignty and the principle of non-intervention in international law. The practice of intervention that is happening now is one of the conversations by the community. The validity of the intervention of other countries is one of them sticking out in the Arab Spring conflict, where Saudi Arabia and Iran make Syria an arena for proxy war where opponents of strength use third parties instead of fighting directly with each other. Saudi Arabia openly supports the opposition in the form of finance, a tool of war. On the other hand, Iran totally supports Bashar al-Assad with financial assistance, weapons of war and sends military forces. This paper analyzes how the position of foreign country intervention in a country's conflict in the study of international law. This paper focuses on the Syrian conflict, the Arab Spring where in the study of international law, intervention is seen as a state effort, and this paper analyzes the legitimacy of the state to carry out such interventions.